Kualitas Pelayanan Program Pendaftaran Tanah Sistematis Lengkap Pada Kantor Pertanahan Kabupaten Sleman - Yanuariza, Yasmin Vitra; Novitaningtyas, Ivo (JPAP: Jurnal Penelitian Administrasi Publik, 2021)
PTSL is a policy implemented by the Government to provide legal certainty and protection for land ownership rights for the community. The BPN Sleman is an institution that also implements the PTSL program. The success of the implementation of the program requires quality service performance in order to provide satisfaction for the community. Therefore, this study aims to determine the quality of the PTSL program in the BPN Sleman in providing services to the community. The research method used in this study is a descriptive analysis method with a qualitative approach. Data collection methods used were observation and interviews during the period of January - February 2020. The Servqual dimension is used as a model to identify the quality of a complete PTSL service. The results of this study explain that the BPN Sleman already provides good quality of services as a whole. The dimensions of tangibles, responsiveness, and empathy tend to have good quality, however, it is necessary to improve the quality of service based on the dimensions of reliability and assurance. The results of this study provide managerial implications for the BPN Sleman to improve the quality of its services to the community, especially in the PTSL program.